(untitled) (Baghdad Science Journal, 2005)
The samples were collected monthly crustaceans Mjmafah foot of two stations in tributary Zab down and two others in the Tigris River for one year with effect from November 2001 until October 2002 recorded during the study period the current 41 units taxonomic and were higher density of Mjmafah foot Guy Tigris River before the mouth of the tributary